1998
DOI: 10.1016/s0028-3932(97)00103-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-domain dissociation between impaired visual perception and preserved mental imagery in a patient with bilateral extrastriate lesions

Abstract: A brain-damaged patient is described whose pattern of performance provides insight into both the functional mechanisms and the neural structures involved in visual mental imagery. The patient became severely agnosic, alexic, achromatopsic and prosopagnosic following bilateral brain lesions in the temporo-occipital cortex. However, her mental imagery for the same visual entities that she could not perceive was perfectly preserved. This clear-cut dissociation held across all the major domains of high-level visio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 51 publications
5
54
1
2
Order By: Relevance
“…Our present results concur with other abundant evidence in suggesting that damage to downstream visual areas located in the temporal lobes is, instead, both necessary and sufficient to produce visual imagery deficits [13,19,43,49,52,54]. In the domain of pure alexia, we see as particularly suggestive the contrast between the patterns of performance of Madame D [3], whose lesions affected BA 18, 19 and 37, and whose visual mental imagery for letters and words was entirely spared (despite her profound alexia), and of VSB, whose lesion extended much more anteriorly into the left temporal lobe, as well as into the parietal lobe, and who showed severely impaired 4 Also, several neuroimaging studies [reviewed in 44] found no evidence of an increased activity in early visual cortices during visual mental imagery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our present results concur with other abundant evidence in suggesting that damage to downstream visual areas located in the temporal lobes is, instead, both necessary and sufficient to produce visual imagery deficits [13,19,43,49,52,54]. In the domain of pure alexia, we see as particularly suggestive the contrast between the patterns of performance of Madame D [3], whose lesions affected BA 18, 19 and 37, and whose visual mental imagery for letters and words was entirely spared (despite her profound alexia), and of VSB, whose lesion extended much more anteriorly into the left temporal lobe, as well as into the parietal lobe, and who showed severely impaired 4 Also, several neuroimaging studies [reviewed in 44] found no evidence of an increased activity in early visual cortices during visual mental imagery.…”
Section: Discussionsupporting
confidence: 92%
“…Why VSB did not spontaneously do so remains an open question (note, however, that after a few testing sessions he did began to spontaneously trace letters and words in the air or on the table, when questioned about their visual form). 3 A reviewer of the present article pointed out that the validity of this patient"s symptoms has been doubted.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We did not have the opportunity to test the patient's knowledge of the visual form of letters in this study, but we did that after her second stroke, and found that Madame D could perfectly conjure up and manipulate mental images of letters (Bartolomeo et al, 1998a). This suggests that her letter identification deficit occurred at a perceptual level of impairment.…”
Section: Summary Of the Findingsmentioning
confidence: 84%